Disseminated cryptococcosis in Crohn's disease: A case report - Natthakit Chavapradit (2019)
© 2018 The Author(s). Background: Gastrointestinal (GI) cryptococcosis is rarely reported. Most cases were diagnosed during evaluation of comorbid conditions, incidental findings, or postmortem. Here, we present a case of Crohn's disease with gastrointestinal cryptococcosis that resembled exacerbation of Crohn's disease. Case presentation: A 64-year-old woman with Crohn's disease (CD) was referred to Siriraj Hospital due to worsening of abdominal pain and watery diarrhea for 2 weeks. The dose of immunosuppressive agents was increased for presumed exacerbation of CD. Pathologic examination of tissue obtained from polypoid mass at ileocecal valve and multiple clean-based ulcers at cecum revealed active ileitis and colitis with multiple round shape organisms with capsule, which was compatible with Cryptococcus species. Disseminated cryptococcosis was diagnosed due to gastrointestinal involvement and presumed pulmonary involvement regarding the presence of an oval-shaped cavitary lesion on chest X-ray and computed tomography of the lung. Patient was successfully treated with amphotericin B followed by fluconazole with satisfactory result. Conclusion: Early diagnosis of gastrointestinal cryptococcosis in Crohn's disease is difficult due to the lack of specific symptoms and sign or mimicking an exacerbation of Crohn's disease. Seeking for other site of involvement in disseminated cryptococcosis including lung or central nervous system as well as detection of serum cryptococcal antigen would be helpful for early diagnosis and management.